Characteristics and Free Radical Scavenging Activity of Zinc Oxide (ZnO) Nanoparticles Derived from Extract of Coriander (Coriandrum sativum L.) - Tagor Marsillam Siregar; Antonius Herry Cahyana; Regina Jessilia Gunawan (Dept. of Chemical Engineering, Diponegoro University, 2017)
Abstract Zinc Oxide (ZnO) nanoparticles were recently studied for its free radical scavenging activity. The formation of ZnO nanoparticles by means of biological method was known to be a simpler and more environmental friendly method. One of the biological methods used for the formation of ZnO nanoparticles was by utilizing the phytochemicals that were present in a plant extract. The phytochemicals such as phenolic and flavonoid compound was able to reduce bulk metal Zinc into Zinc nanoparticles. Coriander (Coriandrum sativum L.) seeds and leaves were known to contain high amounts of phenolic compounds and flavonoid compounds. The aim of this study was to investigate the effect of different solvent polarities used to extract Coriander leaves and seeds towards the reducing power of plant extract and the free radical scavenging capacity of ZnO nanoparticles. The different solvents that were used to extract Coriander were deionized water, ethyl acetate, and hexane. The different solvent polarities affected the weight of the derived ZnO nanoparticles due to the different types of the extracted phenolic and flavonoid compounds. The different solvent polarities also affected the free radical scavenging capacity of ZnO nanoparticles. Ethyl acetate based extract of Coriander leaf resulted in the most weight of ZnO nanoparticles, 0.7907 g and the highest free radical scavenging capacity, 11.16%/mg ZnO nanoparticles. The free radical scavenging activity of ZnO nanoparticles decreased to 3.67%/mg ZnO nanoparticles after the process of calcination at 100°C and decreases to 0 %/mg ZnO nanoparticles after the process of calcination at 300 and 500°C. The diameter of ZnO particles increases from 128.1±33.5 nm to 552.3±61.1 nm after calcination. Kata kunci: calcination; free radical scavenging capacity; polarities; zinc oxide nanoparticles Abstrak KARAKTERISTIK DAN AKTIVITAS PENANGKAL RADIKAL BEBAS NANOPARTIKEL SENG OKSIDA (ZnO) YANG DIBENTUK MENGGUNAKAN EKSTRAK KETUMBAR (Coriandrum sativum L.). Nanopartikel Seng Oksida (ZnO) saat ini tengah diteliti sehubungan dengan kapasitasnya dalam menangkal radikal bebas. Metode biologis merupakan metode sederhana dan ramah lingkungan yang dapat digunakan pada pembentukan nanopartikel ZnO. Pemanfaatan senyawa fitokimia dari ekstrak tanaman merupakan salah satu metode biologis yang dapat digunakan pada pembentukan nanopartikel ZnO. Senyawa fitokimia seperti senyawa fenolik dan flavonoid dapat mereduksi logam Seng menjadi nanopartikel Seng. Biji dan daun dari tanaman ketumbar (Coriandrum sativum L.) telah diketahui memiliki kandungan senyawa fenolik dan flavonoid. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh perbedaan polaritas pelarut yang digunakan untuk ekstraksi biji dan daun ketumbar terhadap kapasitas reduksi ekstrak dan penangkal radikal bebas dari nanopartikel ZnO. Pelarut yang digunakan pada ekstraksi biji dan daun ketumbar adalah air deionisasi, etil asetat dan heksana. Perbedaan polaritas pelarut mempengaruhi berat nanopartikel ZnO yang diperoleh, hal ini disebabkan oleh perbedaan jenis senyawa fenolik dan flavonoid yang terekstrak. Perbedaan polaritas pelarut juga mempengaruhi kapasitas penangkal radikal bebas dari nanopartikel ZnO. Ekstrak etil asetat daun ketumbar menghasilkan nanopartikel ZnO dengan berat 0,7907 g dan aktivitas penangkal radikal bebas sebesar 11,16%/mg nanopartikel ZnO. Aktivitas penangkal radikal bebas nanopartikel ZnO menurun menjadi 3,67%/mg nanopartikel ZnO setelah dikalsinasi pada suhu 100oC dan menurun menjadi 0%/mg nanopartikel ZnO setelah dikalsinasi pada suhu 300oC, 500oC. Diameter nanopartikel ZnO meningkat dari 128,1±33,5 nm menjadi 552,3±61,1 nm setelah dikalsinasi Keywords: elektrokoagulasi, penurunan warna, penurunan TSS, laju degradasi COD, imbah tekstil